Meaningful Relationships: Cruxes of University-Community Partnerships for Sustainable and Happy Engagement - Trae Stewart; Megan Alrutz (The University of Alabama, 2022)
The authors draw on organizational theory's use of the metaphor as a way of understanding and explaining sustainable university/community-engaged partnerships. Working from the premise that transformative and reciprocal relationships prove essential to pedagogies of engagement, specifically service-learning, this essay argues that pursuing and maintaining meaningful partnerships between universities and communities or organizations in many ways parallels our efforts to sustain healthy romantic relationships. Through a description and analysis of 10 cruxes for sustaining long-term, healthy relationships, the authors offer a model for achieving intentional, ongoing, and systemic campus-community partnerships.